China – Tariff Rate Quotas for Certain Agricultural Products. Against the Grain: Can the WTO Open Chinese Markets? A Contaminated Experiment. Issue 4 (21st October 2021) - Glauber, Joseph; Lester, Simon
Abstract: The US complaint about Chinese tariff-rate quotas (TRQs) on certain grain products helps illustrate several key issues in US–China trade relations and the effectiveness of WTO disputes. First, do international obligations based on transparency and fairness work in relation to an authoritarian country not known for the rule of law domestically? Second, can there be a disconnect between the legal aspects of a dispute and the underlying economic interests, with a DSB ruling sometimes not leading to improved trade flows? And third, given the bilateral trade war and 'phase one' trade deal between the United States and China, has the WTO been superseded in this trade relationship? This paper summarizes the facts and law of the China–TRQs dispute, and examines each of these questions in that context.